1981
DOI: 10.1007/bf00434386
|View full text |Cite
|
Sign up to set email alerts
|

The use of four-drug combination chemotherapy (D.A.V.E.) in the treatment of advanced Wilms' tumour

Abstract: A study was begun in 1971 at St. Bartholomew's Hospital with a combination of 4 drugs, dactinomycin (actinomycin D), adriamycin, vincristine and Endoxan (cyclophosphamide) (D.A.V.E.), together with surgery and radiation, in the treatment of stage III and stage IV Wilms' tumour. Seventy-one percent of the children treated achieved complete response. The median survival from diagnosis was 19 months, and in those children achieving complete response the median disease-free survival has not yet been reached. Toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…During the 1960s actinomycin-D was found to be an effective drug and the second National Wilms' Tumor Study reported that a combination of vincristine and actinomycin-D was superior to either agent used singly (D'Angio et al, 1976). For late disease, a 3 or 4 drug combination is used, adding doxorubicin hydrochloride and cyclophosphamide (Dunger et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…During the 1960s actinomycin-D was found to be an effective drug and the second National Wilms' Tumor Study reported that a combination of vincristine and actinomycin-D was superior to either agent used singly (D'Angio et al, 1976). For late disease, a 3 or 4 drug combination is used, adding doxorubicin hydrochloride and cyclophosphamide (Dunger et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…. When a four-agent chemotherapy was adminis tered, however, the tumor-free 2-year survival rate was also improved to 60% for stages III and IV [12].…”
Section: Case Reportsmentioning
confidence: 99%
“…Postoperatively, a subcutaneous wound abscess as well as an acute deep pelvic vein thrombosis of the left side occurred; on the 3rd postoperative day, a four-agent chemotherapy according to a modified soft tissue tumor scheme for metastatic nephroblastomas using vincristine, actinomycin D, adriamycin and cyclophospha mide [12] was started. Simultaneously, telecobalt radiation of the skull up to a focal dose of 30 Gy was applied.…”
Section: Case Reportsmentioning
confidence: 99%
“…Buhles and Shifrine (1) found a rapid restoration of the number of peripheral blood granulocytes in CY-treated mice receiving Mycobacterium bovis BCG or Freund complete adjuvant and suggested that the adjuvant protection against bacterial infection in CY-treated mice may be due in part to the stimulation of the production of progenitor cells of granulocytes by the adjuvants. CY has been used widely as an anticancer drug (4,7,18) and is known to reduce ultimately the host defense to microbial infections. L18-MDP(Ala) may be useful for treating infections occurring in such cancer patients.…”
mentioning
confidence: 99%